Measurement and improvement of the happiness. Case study: engineering projects employees (2019)
The construction of civil works is the development index of a nation, in countries like Colombia, this sector depends on the human factor, which is why it is of utmost importance that employees are happy in carrying out their daily activities. Due to this, this study was developed to measure the degree of job satisfaction on a scale of five response levels in a civil works construction company, where the concepts of the vertical workload theory were applied, through the which, they indicated their degree of satisfaction. The results obtained reveal that, at the beginning of each workday, the boss should hold meetings with the intention of motivating. In addition, he should carry out group recreational activities or active breaks so that the work environment improves continuously and a better performance of the workers, which will allow a high probability of increasing the company's productivity.